Impact of Human Resource Practices on Bank Employees Job Satisfaction - Muhammad Zool Hilmi, Md. Aris (2012)
The purpose of this study is to determine impact of human resource practices on bank employees job satisfaction among the Public Bank’s employees. This study aims to determine does human resource practice affect the bank employees job satisfaction in Public Bank Berhad, and which human resource practices has the most impact in determining bank employees job satisfaction. The survey was carried out at Public Bank Berhad, Ipoh Garden Branch. A total of 50 bank employees participated in this study. Data was collected through 44 items questionnaires on a five-point Likert Scale. Both descriptive and inferential statistics were used to analyze the data using the SPSS version 16.0. The data was analyzed using reliability test, descriptive statistics, T-Test and regression analysis. Overall the findings of this study showed that human resource practices has little impact or affect on the job satisfaction of bank employees in Public Bank Berhad. The study also showed that recruitment and selection has the most impact on bank employees job satisfaction in Public Bank Berhad.